Role of paraventricular and dorsomedial nuclei of the hypothalamus and central nucleus of the amygdala on muscimol-induced cardiovascular responses - (:unkn) unknown (Blackwell Publishing Ltd, 1997)
Gamma-aminobutyric acid (GABA) plays an important role in the central control of cardiovascular functions. Previous evidence indicates that a tonically active GABAergic system exists in forebrain structures. The purpose of this study was to examine the role of the unilateral lesion of the central nucleus of amygdala, paraventricular or dorsomedial nuclei of the hypothalamus on muscimol-induced cardiovascular responses. Electrolytic ablation of nuclei was made by a monopolar isolated electrode under a stereotaxic instrument, 3-5 days before the experiments. Effects of intracerebroventricular injections of muscimol were investigated in intact, lesioned and sham-lesioned rats. On the day of the experiments, blood pressure and heart rate recordings were carried out in male Sprague-Dawley conscious rats. Muscimol produced decreases in arterial blood pressure and heart rate. The hypotensive effect of muscimol was completely inhibited in rats with dorsomedial nucleus lesions, whereas the bradycardic effect was partially prevented. The results indicate that the dorsomedial nucleus of the hypothalamus plays an important role on muscimol-induced blood pressure and heart rate responses.
Keywords: Amygdala; Blood pressure; GABA; Heart rate; Hypothalamus; Muscimol